PENGARUH BUDAYA BIROKRASI TERHADAP KINERJA APARATUR DI SEKRETARIAT DAERAH KABUPATEN BOLAANG MONGONDOW UTARA - Lenda, Siti Nurlily (ACTA DIURNA KOMUNIKASI, 2013)
This research leaves of mark sense that problem indication strong organisational culture and adaptif was maximal developed and is practiced on bureaucracy. This research intent to answer question “in as much as which influence culturizes bureaucracy to apparatus performance at Regency Region secretariat Bolaang Mongondow North. Observational method that is utilized is quantitative method. Data source / respondent penelitin is as much 36 clerks which taken by random's alae of 72 Regency Region secretariat clerks Bolaang Mongondow North. Data collecting utilizes kuesioner and helped by interview tech. analisis's tech that is utilized for hypthosts testing is analisis statistic product moment's linear regression and correlation. Analisis's result data points out: (1 ) variable's regression coefficients culturizes bureaucracies to positive apparatus and signifikan on signifikan's level 0,01atau is trust level 99%. (2 ) correlation coefficient and variable's determinant coefficient culturizes bureaucracies to apparatus performances be signifikan on signifikan's level 0,01 or trust level 99%. Base that observational result concluded that positive influential bureaucracy culture and signifikan to apparatus performance; its mean getting better and bureaucracy culture positive therefore getting better too apparatus performance. Leave from observational result conclusion therefore suggested to increase organisational culture implement that strong and adaptif on bureaucracy utilisedding to increase apparatus performance. Key word:bureaucracy culture, apparatus performance.